PTH-106 Phenotypic characterisation of elderly – onset inflammatory bowel disease – ibd at 60 and beyond. (17th June 2017) - Nosegbe, U; Miller, B; Crooks, B; Scott, J; Limdi, J
Abstract : Introduction: The incidence of inflammatory bowel disease (IBD) is increasing globally in all age groups however data on elderly onset IBD (age 60 and over) is limited. We aimed to study the phenotypic characteristics of elderly onset IBD. Method: A retrospective analysis of 142 patients diagnosed with IBD at 60 years or above at our institution between 1995 and 2016 was conducted. Electronic case notes were reviewed to collect data on demographics, Montreal classification and treatment Results: Of 142 patients in our cohort, 71 were male. Median age was 71 years (range 62–91) and median age at diagnosis was 65 years (range 60–85). 50 patients had Crohn's disease (CD) (35.2%), 81 Ulcerative colitis (UC) (57.0%) and 11 (7.8%) IBD-unspecified (IBDU). Montreal classification for UC was proctitis (E1) in 27, left sided colitis (E2) in 30 and pancolitis (E3) in 22. Two patients with proctosigmoiditis await classification. Montreal classification for CD was ileal structuring (L1 B2) in 18 : colonic (L2 B1 in 14 patients and L2 B2 in 5 patients. Ileo-colonic (L3) disease was found in 12 (7 B1 and 5 B2) patients. At diagnosis 88 patients were prescribed 5ASA's (18 topical and 6 combined with oral 5ASA's). Corticosteroids were prescribed at diagnosis in 44 (31.4%) patients. Azathioprine was used in 3 (2 E3 and 1 L2B2) patients and 3 patients commenced Infliximab at diagnosis (L3B1 and L1B2 CD and E3 UC). At most recent follow up 26 patients were on corticosteroids, 35 were on immunomodulation (26 on Azathioprine, 5 on 6MP and 4 on Methotrexate) with a mean time to immunomodulation being 29.4 months (range 0–137). 16 were on biologics (14 Infliximab and 2 Adalimumab) with a mean time to therapy of 33.7 months (range 0–189 months). 15 patients (10.7%) had surgery related to IBD: 2 UC vs 13 CD and median time to surgery was 20 months (range 0–132 with 2 patients being diagnosed at initial surgery). Colon cancer was diagnosed in 1 patient with L2B1 and curative resection was undertaken. 4 deaths occurred: 1 from CLL (not on immunomodulation), 1 klebsiella pneumonia on Azathioprine, 1 from cryptococcal meningitis on Azathioprine and Infliximab and 1 from prostate cancer. Conclusion: We noted a higher prevalence of UC with E2 and E3 disease and a colonic phenotype in CD corroborating with data from the EPIMAD registry 1 .. A large proportion of patients received immunomodulation which is an area of concern and needs careful consideration There is an urgent need for more data on disease presentation, natural history and treatment paradigms for the considered and optimal management of elderly patients with IBD. Reference: Charpentier C, et al. Natural history of elderly-onset inflammatory bowel disease: a population-based cohort study. Gut2014;63(3):423–32 Disclosure of Interest: None Declared